AGV vehicle differential drive model. Issue 1 (June 2021) - Yao, Yi; Sun, Ye
Abstract: Based on the establishment and analysis of the position model and forward kinematics model of the AGV vehicle, this paper derives the motion trajectory and related motion parameters of the fixed standard wheel and the manipulated standard wheel, and analyzes the motion of the AGV vehicle based on the specific motion parameters, to obtain the constraint sum of the motion and rolling and sliding of the differential AGV vehicle, and the relationship between the wheel speed of the AGV vehicle.